Teaching International Relations with OBE Curriculum and Contribution to Environmental Politics: A Case Study of Asta Bhumi Community in Supporting SDG 4 - Masitoh Nur Rohma (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: Higher education requires learning approaches that not only focus on knowledge acquisition but also develop students’ competencies to apply knowledge in real-world contexts. This study aims to analyze the implementation of Outcome-Based Education (OBE) in the International Relations Study Program at Universitas Islam Indonesia through the Environmental Politics in International Relations course and its contribution to student learning outcomes. This study supports SDG 4 (Quality Education) by emphasizing the importance of competency-based and student-centered learning. Method: A qualitative case study approach. Data were collected through observation, document analysis, and interviews with students involved in the Environmental Politics in International Relations course and the establishment of the Asta Bhumi Community. Data analysis focused on the implementation of OBE principles through the learning performance pyramid, including knowledge, competence, and confidence. Results: The findings show that OBE implementation enabled students to transform theoretical knowledge into meaningful actions. Students developed competencies related to sustainable development, environmental issues, and environmental diplomacy, which were implemented through the formation of the Asta Bhumi Community.. Novelty: This study highlights how OBE can strengthen educational quality by connecting curriculum implementation with students’ ability to produce tangible outcomes. The findings demonstrate that quality education should enable students not only to understand knowledge but also to apply competencies in addressing real-world challenges.